Improving biodiesel stability via glycerol-donated catalytic transfer hydrogenation for sustainable biofuel refinery - Aqsha Aqsha; Muhammad Naufaal Daffa Realdi; Novin Isra Herdian; Kholidatul Fauziyah Nursaid; Candra Egiyawati; Yano Surya Pradana; Andreas Yulius Pamungkas; Jenny Rizkiana; Tatang Hernas Soerawidjaja; I Gusti Bagus Ngurah Makertihartha; Wan Hanna Melini Wan Mohtar; Antonius Indarto (Discover Sustainability)
Abstract This study investigated the application of catalytic transfer hydrogenation (CTH) using glycerol as a hydrogen donor and bimetallic catalysts at mild temperature and atmospheric pressure to enhance biodiesel oxidation stability. In this process, hydrogen atoms derived from glycerol were utilized to reduce double bonds in unsaturated fatty acid methyl esters. The effectiveness of this reaction was evaluated through the changes in iodine value, peroxide value, oxidation stability, and composition of biodiesel product. Under nitrogen purging, the application of Ni-Fe-Iz catalyst effectively improved biodiesel oxidation stability by 1.02 h, reduced iodine value by 0.14 g I2/100 g, and alleviated peroxide value by 19.77 meq O2/kg. Additionally, this study further indicated that the removal of residual metal catalysts and the prevention of oxygen exposure during reaction avoided negative effects on biodiesel oxidation stability. Finally, these findings demonstrate that CTH technique using glycerol and Ni-Fe-Iz catalyst is a promising and more sustainable alternative to conventional hydrogenation, eliminating reliance on external hydrogen gas and high-pressure systems.